Estudio de la norma ISO 14001:2015 en un sistema de generación de biogás a partir de desechos orgánicos. (2022)
The research focused on the applicability of the International Standard ISO 14001:2015 in the improvement of the environmental management system for the generation of non-conventional renewable sources, the most important in this study being the production of biogas from organic solid waste, initially A bibliographic review of the production, export and import of traditional energy sources that do so much damage to the environment is carried out and likewise seek alternatives for continuous improvement with the implementation of renewable energy sources using accumulated waste especially in the primary sector. In addition, different biogas production processes are evaluated with their respective composition and valuation in the market with the removal of contaminants that affect the product of interest in order to develop a plan for continuous improvement in the environmental management system, taking as a point of reference the pollution generated in the environment and likewise constitute a company given as an example to evaluate the effectiveness of ISO 14001: 2015 in the development and growth in the market, obtaining as a result an evaluation in the environmental management of a company and likewise implement the guidelines established in this study, such as the DOFA management and analysis indicators for risk minimization and waste accumulation due to poor handling of raw materials and in the production of the product of interest.